The effect of electonic word of mouth, destination social responsibility, destination image, and destination trust on intention to visit on Kinantan wildlife and culture tourism object at Bukittinggi - Maratul Khairani Pardila; Abror Abror (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze: the effect of electronic word of mouth, destination social responsibility, destination image, and destination trust on the intention to visit the Kinantan Cultural and Wildlife Park tourism object, Bukittinggi city. The method used is quantitative. The population of this study were all domestic tourists in West Sumatra who had never visited the Kinantan Cultural and Wildlife Park in Bukittinggi City. The sample of this study was 280 people. This study uses Structural Equation Model (SEM) analysis as a data analysis tool. The results showed that: (1) Electronic Word of Mouth had a significant effect on Destination Image, (2) Electronic Word of Mouth had a significant effect on Destination Trust, (3) Destination Social Responsibility had a significant effect on Destination Image, (4) Destination Social Responsibility had a significant effect on significant effect on Destination Trust, (5) Destination Image has a significant effect on Destination Trust, (6) Destination Image has a significant effect on Intention to Visit, (7) Destination Trust has a significant effect on Intention to Visit.